Analysis of Maternal Deaths Trends in Bojonegoro, Indonesia - Mariya Ulfah, -
Abstract Maternal Mortality Rate (MMR) could indicate the welfare of a nation. In ASEAN, Indonesia ranks as the highest number of MMR. Furthermore, in Bojonegoro Regency, the MMR ranked 4th in East Java Province after Surabaya, Jember, and Sidoarjo. Indirect causes of maternal deaths consisted of three delays: 1) maternal referral delay; 2) delay in recognizing problems and making decisions; and 3) delay in reaching health facilities and getting services. These three delays are the leading causes of the increase in maternal mortality in Bojonegoro Regency. This study aims to analyze the trends in the number of maternal deaths and predict the occurrence of death in the following year. The data consist of maternal mortality cases for the period 2008-2017, and it analyzed by four trend analysis and compared by the MAPE, MAD, and MSD values for each method. The results show that the two categories use the Quadratic Trend Model precisely. Forecasting results in 2018 are estimated to have decreased maternal mortality by 11.76% from 2017, and in 2019 it is estimated to increase by 33.33%. These results indicate that maternal mortality in Bojonegoro still needs to be anticipated.